2000
DOI: 10.1021/om0004702
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Iron(0) Complexes Derived from α,β-Unsaturated-Ketone Analogues with β-Positioned Heteroatoms Containing Covalent and Coordination Bonds

Abstract: Synthesis of novel mono-and dinuclear complexes of Fe(0) are reported displaying both coordination and organometallic bonds. 5-11 were prepared by allowing the new ligands 1-4 to react with Fe 2 (CO) 9 . The structures of the complexes were determined by spectroscopic methods (IR, MS, HR-MS, 1 H and 13 C NMR) and confirmed by single-crystal X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Our interest in the iron chemistry led us to synthesize new mono and dinuclear Fe(0) complexes which have been prepared by reaction of a,b-unsaturated-ketones analogues containing b-positioned heteroatoms with Fe 2 (CO) 9 [5][6][7][8]. In connection with these studies, we have reported that a,b-unsaturated ligands possessing the dithiol group reacts with diiron nonacarbonyl affording dinuclear complexes (a) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the iron chemistry led us to synthesize new mono and dinuclear Fe(0) complexes which have been prepared by reaction of a,b-unsaturated-ketones analogues containing b-positioned heteroatoms with Fe 2 (CO) 9 [5][6][7][8]. In connection with these studies, we have reported that a,b-unsaturated ligands possessing the dithiol group reacts with diiron nonacarbonyl affording dinuclear complexes (a) [6].…”
Section: Introductionmentioning
confidence: 99%
“…They have the same structural arrangement as the complex 1c, previously reported. 6,11 The IR spectra of these compounds show the typical bands of (M-CO) in 2058 and 2017 cm -1 . The 1 H NMR spectra of 3c and 4c exhibit changes in the assigned signals to the methylene groups, which shifted upfield with respect to ligands.…”
Section: Resultsmentioning
confidence: 97%
“…These features indicate that an interaction between the sulfur and oxygen atoms through the conjugated system is present, in agreement with the obtained results from IR technique and with described in literature. 6,7 The 1,3-dithiolane ring adopts a half-chair conformation with C 2 axe over C11. Additionally, this moiety presents disorder generating two conformers in 46/54 ratio, only the major contributors are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations